Practice and Knowledge of Health Personnel on Impact of Medical Wastes in Upazilla Health Complexes under Dhaka Division in Bangladesh (City Dental College Journal, 2018)
A cross-sectional study was conducted among 42 health personnel and people without a medical background but concerned with the waste management. They were interviewed through pretested semistructured questionnaires at their working places of the upazilla health complexes at Sreepur, Kapasia, Kaligonj, Shivaloya, Saturia, Savar and Dhamrai under Dhaka division of Bangladesh. A total of 6 respondents (2 doctors, 2 nurses and 2 support staff) from each of the upazillas were recruited. Upazilla health complexes were running with average bed occupancy of ?10/day and where ?10 health personnel were working. The objective of this study was to assess the practice and knowledge on impact of the medical wastes of the health personnel working in the health complexes. The distribution of the respondents by their responses regarding environmental impact of medical wastes were recorded, analyzed and tabulated. Hundred percent (100.0%) respondents said about pollution of air, 89.7% said about pollution of surface water, 69.0% said about pollution of ground water, 58.6% said about open dump with infectious agents, soil pollution, 48.3% said about enhance spread of infectious diseases by rodent, 34.5% said about litter and leachate, 20.7% said about production of methane and greenhouse gases and 10.3% said about raised environmental temperature due to the increase of greenhouse gases. Regarding the knowledge of environmental impact of medical wastes, doctors and nurses were found to be more knowledgeable than the support staff. The difference was found to be statistically significant. DOI: http://dx.doi.org/10.3329/cdcj.v10i1.13830 City Dent. Coll. J Volume-10, Number-1, January-2013